Functional characterization of the developmentally controlled immunoglobulin kappa 3' enhancer: regulation by Id, a repressor of helix-loop-helix transcription factors. - Pongubala, J M (1991)
We have functionally characterized an enhancer element (kappa E3') which lies 8.5 kb downstream of the immunoglobulin kappa gene. The activity of this enhancer is developmentally controlled. It is inactive at the pre-B-cell stage but active at the B-cell and plasma cell stages. This enhancer is also functional in S107 plasmacytoma cells, which lack NF-kappa B and therefore intron enhancer activity. The activity of the kappa E3' enhancer therefore provides an explanation for the transcriptional activity of endogenous kappa genes in S107 cells in the absence of intron enhancer function. We have identified a 132-bp segment of the kappa E3' enhancer that retains 75% of the activity of the entire enhancer observed in plasmacytoma cells. Within this 132-bp core, there are at least two functional elements, one of which binds to a B-cell-specific nuclear factor. This element contains a potential binding site for the B-cell- and macrophage-specific transcription factor PU.1. The kappa intron and kappa E3' enhancers were also found to be regulatable by Id, an inhibitor of helix-loop-helix transcription factors. The site of action of Id on the kappa E3' enhancer was mapped to a 25-bp region which contains a potential binding site for a helix-loop-helix transcription factor. A possible model for the developmental control of kappa gene transcription is discussed.